Uczestnictwo dzieci w młodszym wieku szkolnym w kulturze muzycznej – codzienność doświadczeń - Majzner, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article attempts to show the everyday experiences of a child at early school age regarding his or her participation in musical culture. Information on the forms of participation in musical culture are based on a survey conducted among parents of children attending the classes I-III of primary school. The results obtained within the research may indicatemost glaring trends regarding the frequency and forms of their creative and receiving contact with musical culture in the opinions of parents.
Keywords: dzieci; kultura muzyczna; muzyka; uczestnictwo bierne; uczestnictwo czynne